Thermal mannequin assessment on different types of building layout towards the impact of UHI penomenon [electronic resource] - Hairul Hasbi, 1990- (2013)
Project Paper (Sarjana Muda Kejuruteraan (Awam)) - Universiti Teknologi Malaysia, 2013